2018
DOI: 10.1177/1460458218799458
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of telemonitoring use by seniors with chronic heart failure: Adoption, self-care, and empowerment

Abstract: Telemonitoring leverages technology for the follow-up of patients with heart failure. Limited evidence exists on how telemonitoring influences senior patients’ attitudes and self-care practices. This study examines telemonitoring impacts on patient empowerment and self-care, and explores adoption factors among senior patients. A longitudinal study design was used, involving three surveys of elderly with chronic heart failure (n = 23) 1 week, 3 months, and 6 months after beginning telemonitoring use. Self-care,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 34 publications
3
24
0
1
Order By: Relevance
“…More recently, Risling et al [ 15 ] found that patients in a digital study identified the relational and informational elements of empowerment and recommended that these key areas should shape the focus of the evolution of patient empowerment in digital research. Telemonitoring has been found to be effective as a confidence, decision-making, and self-care enhancer in older persons with chronic heart failure [ 16 , 17 ]. Telemonitoring surveillance systems have left patients with feelings of greater self-control, heightened motivation for lifestyle changes, and improved quality of life [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Risling et al [ 15 ] found that patients in a digital study identified the relational and informational elements of empowerment and recommended that these key areas should shape the focus of the evolution of patient empowerment in digital research. Telemonitoring has been found to be effective as a confidence, decision-making, and self-care enhancer in older persons with chronic heart failure [ 16 , 17 ]. Telemonitoring surveillance systems have left patients with feelings of greater self-control, heightened motivation for lifestyle changes, and improved quality of life [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, patients performed less self-care maintenance activities, and the capability of involvement in the decision-making related to their condition decreased. 29 Despite the increasing confidence of patients in identifying and evaluating their own symptoms, self-care behaviors have been reduced. The reasons for this can be a small sample size (23 patients) and a lack of control group.…”
Section: Enrollmentmentioning
confidence: 99%
“…Various studies have reported the effectiveness of telemonitoring in reducing mortality, [2][3][4] hospitalizations and emergency department visits, 4,5 as well as improving patient perceived quality of life, 6 evidence-based prescribing and overall management of disease. 7,8 While the effectiveness of home telemonitoring on clinical outcomes and health care costs have been widely explored, the evaluation of home telemonitoring has been expanded to include user experience, 9,10 perceived impact and organizational analysis. 2,11 Telemonitoring does not just "work" or "not work" 12 as the success of telemonitoring depends on many factors, including organization of the telemonitoring program, technology complexity, patients' compliance, and how clinicians and patients are engaged.…”
Section: Introductionmentioning
confidence: 99%